2023
DOI: 10.3390/nano13081383
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial-Reinforced Portland-Cement-Based Materials: A Review

Abstract: Portland cement (PC) is a material that is indispensable for satisfying recent urban requirements, which demands infrastructure with adequate mechanical and durable properties. In this context, building construction has employed nanomaterials (e.g., oxide metals, carbon, and industrial/agro-industrial waste) as partial replacements for PC to obtain construction materials with better performance than those manufactured using only PC. Therefore, in this study, the properties of fresh and hardened states of nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…However, findings from various researchers [24,[67][68][69] indicate that the relevant delay may be attributed to the nucleation problem of C-S-H products rather than the dissolution problem. Research conducted by FrancoLujan et al [70] showed that the dynamic interaction between dissolution and nucleation could be significant. On the other hand, mortars with green synthesized NAs did not show broad delay times, and setting times were closer to the reference results, regardless of the sample type.…”
Section: Mortar Strength Setting Times and Durability Studiesmentioning
confidence: 99%
“…However, findings from various researchers [24,[67][68][69] indicate that the relevant delay may be attributed to the nucleation problem of C-S-H products rather than the dissolution problem. Research conducted by FrancoLujan et al [70] showed that the dynamic interaction between dissolution and nucleation could be significant. On the other hand, mortars with green synthesized NAs did not show broad delay times, and setting times were closer to the reference results, regardless of the sample type.…”
Section: Mortar Strength Setting Times and Durability Studiesmentioning
confidence: 99%
“…Although this goes beyond the focus of this article, it is worth discussing due to the concerns expressed by both technical and academic communities. Two research topics can be highlighted: (i) Substituting a percentage of conventional cement with other materials, such as nanomaterials, to reduce CO 2 emissions by decreasing the production of Portland cement and enhancing the resilience of Portland cement-based concretes against hazards such as fire, earthquakes, and aggressive industrial environments (e.g., [46]; (ii) Making efforts to properly rehabilitate existing reinforced concrete (RC) buildings in terms of seismic performance (e.g., [47,48]) and considering the use of more efficient and thinner concrete jackets (e.g., [49][50][51][52]).…”
Section: Approach Energy Policy Documentsmentioning
confidence: 99%
“…Knowledge related to these aspects is critical, as the amount of nano-admixtures used for radiation shielding purposes usually exceeds the optimal value for ensuring proper mechanical and durability performance of cement-based composites. It is widely agreed that, typically, the optimal content of nanoparticles lies within the range of 0.5 to 5% mass of binder [ 44 , 45 , 46 ]. However, for radiation shielding applications, the amount of a single nano-admixture frequently ranges between 3 and 10 wt% [ 8 , 10 , 12 , 13 , 14 , 17 , 47 ], therefore, higher replacement rates of a binder with nanoparticles might lead to undesirable alterations in the hydration process of cementitious systems.…”
Section: Introductionmentioning
confidence: 99%